Overexpression of miR-223 Promotes Tolerogenic Properties of Dendritic Cells Involved in Heart Transplantation Tolerance by Targeting Irak1 - Yuan, Shun; Chen, Yuanyang; Zhang, Min; Wang, Zhiwei; Hu, Zhipeng; Ruan, Yongle; Ren, Zongli; Shi, Feng (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are key mediators of transplant rejection. Numerous factors have been identified in regulation of transplant immunopathology by modulating the function of DCs. Among these, microRNAs (miRNAs) are small non-coding RNA molecules which have got much attention. MiR-223 in particular, is very highly expressed and tightly regulated in hematopoietic cells. It plays a important role in modulating the immune response through regulating the functions of the neutrophils and macrophages and its dysregulation has been demonstrated to contribute to multiple types immune diseases. However, the role of miR-223 in immune rejection response is unclear. Here, we have found that miR-223 expression increased in the serum of patients and mice after heart transplantation and heart grafts of mice. We isolated DCs and T cells from spleens of recipient mice, and found that miR-223 expression was significantly increased in DCs, whereas expression of miR-223 in T cells was unchanged. What’s more, we have demonstrated that miR-223 expression decreased in LPS-stimulated DCs. Increasing miR-223 expression in DCs promotes the polarization of DCs towards a tolerogenic DCs (tDCs) phenotype, which indicates that miR-223 can attenuate activation and maturation status of DCs. MiR-223 effectively induced regulatory T cells (Tregs) generation by inhibiting the function of antigen-presenting DCs. In addition, we identified Irak1 as a genuine miR-223 target gene and an essential regulator for DCs maturation. In a mouse allogeneic heterotopic heart transplantation model, grafts in the miR-223-overexpressing imDCs group survived longer and suffered less immune cells infiltration. In miR-223-overexpressing imDCs recipients, T cells in spleens were significantly differentiated into Tregs, and the levels of IL-10 in heart grafts were markedly higher than those in the control group. In conclusion, miR-223 regulates the function of DCs via Irak1, inducing Tregs differentiation and IL-10 secretion, thereby suppressing allogeneic heart graft rejection.